1996
DOI: 10.1523/jneurosci.16-14-04449.1996
|View full text |Cite
|
Sign up to set email alerts
|

Double Transduction with GTP Cyclohydrolase I and Tyrosine Hydroxylase Is Necessary for Spontaneous Synthesis ofl-DOPA by Primary Fibroblasts

Abstract: Gene transfer of tyrosine hydroxylase (TH) in animal models of Parkinson's disease (PD), using either genetically modified cells or recombinant virus vectors, has produced partial restoration of behavioral and biochemical deficits. The limited success of this approach may be related to the availability of the cofactor, tetrahydrobiopterin (BH4), because neither the dopamine-depleted striatum nor the cells used for gene transfer possess a sufficient amount of BH4 to support TH activity. To determine the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
92
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 48 publications
7
92
0
Order By: Relevance
“…Therefore, for subsequent experiments, this copy number was used for double transfection (multifection) in order to yield maximal gene transfer. Double transduction/transfection is routinely used for many viral as well as non-viral genetic modification approaches such as lipid-mediated gene delivery and electroporation in order to enhance transfection efficiency and to prolong gene expression [37][38][39]. We previously showed that multifection of NSCs (cultured as 3-D neurospheres) resulted in higher transfection levels (~27%) compared to single transfection (~13%) with no effect on cell physiology and health [22].…”
Section: Minicircle Use With Magnetofection Dramatically Enhances Nscmentioning
confidence: 99%
“…Therefore, for subsequent experiments, this copy number was used for double transfection (multifection) in order to yield maximal gene transfer. Double transduction/transfection is routinely used for many viral as well as non-viral genetic modification approaches such as lipid-mediated gene delivery and electroporation in order to enhance transfection efficiency and to prolong gene expression [37][38][39]. We previously showed that multifection of NSCs (cultured as 3-D neurospheres) resulted in higher transfection levels (~27%) compared to single transfection (~13%) with no effect on cell physiology and health [22].…”
Section: Minicircle Use With Magnetofection Dramatically Enhances Nscmentioning
confidence: 99%
“…In addition, instead of integrating with host brain circuitry, they tend to displace the brain parenchyma by forming a globular clump of cells, which itself can disrupt rotational behavior in rodents. 13 Astrocytes also potentially represent an autologous source of cell vehicles. 14 They have been tested owing to their natural supportive role in the brain, their efficient secretory mechanisms, transducibility in vitro, and tendency to migrate from the graft site, thus minimizing mass effect.…”
Section: Gene Therapy For Parkinson's Disease (Pd)mentioning
confidence: 99%
“…30 -33 Early approaches to delivering TH cDNA in the striatum of animal models of PD have included the in vivo injection of viral vectors HSV-1, AAV, and adenovirus. 34 -37 Ex vivo engineering of cell lines, primary cells, 5,13,17 and immortalized cell lines generated from embryonic mesencephalic cultures have also been used in ex vivo gene transfer studies, 9 with various degrees of functional effects, none sufficient to advance to clinical testing.…”
Section: Gene Therapy For Parkinson's Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Procedures include direct transfer in vivo of the TH cDNA to striatal cells via viral vectors, 54,135,[142][143][144] transplanting cells which have been transduced ex vivo to express TH, 87,[145][146][147][148][149][150] and administration of a DNA-liposome complex encoding TH. [151][152][153] More recently the full pathway of DA synthesis been included in this approach, with the additional transfer of the synthetic enzyme GTPcyclohydrolase (GTPCH) to generate the TH cofactor, tetrahydrobiopterin, 55,[154][155][156] as well as transfer of aromatic amino acid decorboxylase (AADC) to facilitate conversion of L-Dopa to DA. [157][158][159] Together these genes may maximize production of DA in the striatum.…”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%